The Relationship of Vitamin A and Neonatal Respiratory Diseases: A Meta‐Analysis - Yuanyuan Li; Ruoyu Zhang; Zhongliang Li; Qingfeng Zhai (The Clinical Respiratory Journal)
ABSTRACT This study systematically analyzes the relationship of vitamin A on the neonatal respiratory diseases. An extensive literature search for relevant studies was conducted on PubMed, Web of Science, and so on. After screening in strict accordance with the inclusion and exclusion criteria, 12 articles on vitamin A deficiency and 12 articles on vitamin A supplementation were included. Stata 17.0 software was used to perform meta‐analysis, heterogeneity test, and sensitivity analysis, and the corresponding mathematical model was used to merge the data. The meta‐analysis results of the relationship between vitamin A deficiency and neonatal respiratory diseases indicated that compared with the neonates with normal vitamin A, the neonates with vitamin A deficiency had adverse health outcomes of neonatal respiratory diseases (OR = 4.86, 95% CI: 2.68–8.84), of which neonatal respiratory distress syndrome (NRDS) (OR = 4.10, 95% CI: 2.32–7.23) and neonatal pneumonia (OR = 3.22, 95% CI: 2.18–4.77) were analyzed by subgroup analysis. The meta‐analysis of the relationship between vitamin A supplementation therapy and neonatal respiratory diseases showed that vitamin A supplementation was an effective therapeutic measure for neonatal respiratory diseases (RR = 1.06, 95% CI: 1.04–1.07): NRDS (RR = 1.03, 95% CI: 1.02–1.05) and NBPD (RR = 1.08, 95% CI: 1.01–1.15). The funnel chart method results show that there was publication bias in studies on vitamin A deficiency induced to and vitamin A supplementation therapy for neonatal respiratory diseases. The sensitivity analysis results showed that excluding some special article had some effect on the final pooled effect. But generally speaking, the result of meta‐analysis was stable. There is a statistical correlation of vitamin A on the neonatal respiratory diseases from two aspects of etiological exploration and effect evaluation of treatment.